Aplikasi Elemen Saintifik Dalam Tafsir Al-quran: Satu Pengamatan Awal Terhadap Manhaj Zaghlul El-Najjar Dalam "Tafsir Al-Ayah Al-Kawniyyah Fi Al-Qur'an Al-Karim - Selamat Amir; Mohd Murshidi Mohd Noor; Ahmad Bazli Ahmad Hilmi (Academy of Islamic Studies, University of Malaya, 2024)
The advancement of science and technology which has been in par with the urbanization of knowledge requires a precise analysis by Muslims in order to have a better understanding of Maqāsid of al-Qur’ān. Thus, the manhaj has been introduced by Prof. Dr. Zaghlūl el-Najjār through his scientific interpretation technique; it can also be found in his work Tafsīr al-Ayah alKawniyyah fī al-Qur’ān al-Karīm which has brought about such a sound impact in the comprehension of bait tauhidik (tauhidic verses). Through the method of scientific data analysis, he tried to study the Qur’ānic verses, in particular al-kawniyyah verses, which they comprise various aspects of creation of the universe, human health and creation. In addition to Najjār’s scientific arguments, the application of classical method in explaining the Qur’ānic verses was also highlighted in his work (particularlly in the textual understanding of the Qur’an). Hence, this article focuses on Zaghlūl al-Najjār’s methodology in his reputed work of Tafsīr al-Ayah al-Kawniyyah fi al-Qur’ān al-Karīm.